1987
DOI: 10.1093/rheumatology/26.1.17
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of the Anticentromere Antibody

Abstract: To elucidate further the clinical significance of the anticentromere antibody (ACA), 32 Australian-born Caucasian patients with scleroderma (SD) or CREST (calcinosis, Raynaud's phenomenon, oesophageal dysmotility, sclerodactyly and telangiectasia) were reclassified as ACA-positive (19 patients) or ACA-negative (13 patients). The clinical features of the two groups were compared. Mean disease duration was 11.7 years for the ACA-positive group and 1.1 years for the ACA-negative group. No ACA-positive patient had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In another study it was suggested that ACA positivity is associated with a more benign form of SSc with limited cutaneous and internal organ involvement. In that study the mean disease duration of ACA-positive patients was found to be markedly longer than that of ACA-negative patients [22].…”
Section: Discussionmentioning
confidence: 72%
“…In another study it was suggested that ACA positivity is associated with a more benign form of SSc with limited cutaneous and internal organ involvement. In that study the mean disease duration of ACA-positive patients was found to be markedly longer than that of ACA-negative patients [22].…”
Section: Discussionmentioning
confidence: 72%
“…At this time, antinuclear antibodies of discrete speckled pattern and anticentromere antibodies were identified. These findings provided clear evidence of CRSTsyndrome (2,12). However, the pattern of liver dysfunction, which consisted of hypergammaglobulinemia, and the elevation of ASTand ALT, had not changed.…”
Section: Case Reportmentioning
confidence: 78%
“…Fortyeight patients (49% of those asked) complained of dyspnoea on exertion, 6 of dyspnoea at rest, 20 (24% of those asked) admitted to dry cough and 10 (12%) to productive cough. Smoking status was recorded for 72 patients: 41 (57%) were nonsmokers, 17 (24%) were ex-smokers and 14 (19%) were current smokers at presentation.…”
Section: Clinical Datamentioning
confidence: 99%